1978
DOI: 10.1111/j.1365-2125.1978.tb01644.x
|View full text |Cite
|
Sign up to set email alerts
|

The second Lilly Prize Lecture, University of Newcastle, July 1977. beta‐Adrenergic receptor blockade in hypertension, past, present and future.

Abstract: All beta‐adrenoceptor blocking drugs that have been described share the common property of being competitive inhibitors. They differ in their associated properties, the presence or absence of cardioselectivity, membrane stabilizing activity, and partial agonist activity. Recently some beta‐adrenoceptor blocking drugs have been reported which also possess alpha‐adrenoceptor blocking activity. The associated properties have been used as a basis for classifying beta‐adrenoceptor blocking drugs (Fitzgerald, 1969, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(3 citation statements)
references
References 178 publications
0
3
0
Order By: Relevance
“…It was also shown that propranolol has anti-arrhythmic properties. Subsequent work established that the anti-hypertensive and anti-arrhythmic properties, together with the reduction in heart rate and cardiac output, are important class actions of β-adrenoceptor antagonists ( Table 1 ) [10] .…”
Section: Early Development and Clinical Uses Of β-Blockersmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that propranolol has anti-arrhythmic properties. Subsequent work established that the anti-hypertensive and anti-arrhythmic properties, together with the reduction in heart rate and cardiac output, are important class actions of β-adrenoceptor antagonists ( Table 1 ) [10] .…”
Section: Early Development and Clinical Uses Of β-Blockersmentioning
confidence: 99%
“…In 1978, Prichard observed: ‘Two important untoward effects from β-adrenergic receptor blocking drugs that should be avoided with foresight in patient selection: heart failure and asthma. Patients in heart failure, or patients with incipient left ventricular insufficiency … are critically dependent on sympathetic activity to the heart to maintain their cardiac output.’ [10] . Indeed, heart failure occurs when the cardiac output is not sufficient to meet the demands of the body so reducing output further with a β-blocker would appear illogical.…”
Section: Heart Failure and β-Blockers: Paradoxical Pharmacology?mentioning
confidence: 99%
“…Prichard classified beta-blockers into three types according to their beta1-selectivity and vasodilatory potential [ 4 ]. An additional classification is lipophilic or hydrophilic beta-blockers [ 5 , 6 ].…”
Section: Hypertensionmentioning
confidence: 99%